An Efficient g-Centroid Location Algorithm for Ptolemaic Graphs - Veeraraghavan, P. (International Symposium on Computer Science and its Applications, 2008)
In an earlier paper by C.Pandu et al (1998), we presented an O(m 2 ) algorithm for locating the g-centroid for ptolemaic graphs. Here we improve the time complexity and propose an efficient O(n 3 )-time algorithm for locating the g-centroid for ptolemaic graphs. This is by defining an auxiliary graph.